ENBAL AS A FOOD SECURITY AND LOCAL INTELLIGENCE IN KEI ISLAND - Hanafi, Bima (Erudio Journal of Educational Innovation, 2024)
Indonesia is one of the countries in the Asia Pacific region that has good food security indicators, but until now local food products have not been able to shift rice and wheat flour which still dominate. The urgency of local food research is very urgent in order to strengthen the treasures of local wisdom in the face of increasingly massive modernization. This research was conducted in Ohoi Langgur, Kei Kecil Sub-district, Southeast Maluku Regency. This research used qualitative method with case study approach and Miles and Huberman interactive analysis model. The results of this research show that; First, according to oral sources, enbal food comes from Bali which was brought by their parents from before the Dutch colonization. Second, there are 2 types of Enbal food processing, namely traditional and modern methods. The traditional process of making Enbal begins with peeling the sweet potato and then grating it using a machine and after that it is put into a bag and then clamped so that it releases toxic water. After drying, the enbal gepe (pinch) is grated so that it is smooth so that it can be used in the processing process. The modern process uses electricity-based electronic equipment. Third, currently new variants of enbal-based dishes have been developed. Fourth, the values contained in enbal food culture are in line with the philosophy of the Kei community, namely Ain Ni Ain, namely the value of solidarity which further strengthens the bonds of brotherhood (social cohesion) of the community, especially among Kei youth.